Routledge international handbook of race, class, and gender - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
The Routledge International Handbook of Race, Class, and Gender chronicles the development, growth, history, impact, and future direction of race, gender, and class studies from a multidisciplinary perspective. The research in this subfield has been wide-ranging, including works in sociology, gender studies, anthropology, political science, social policy, history, and public health. As a result, the interdisciplinary nature of race, gender, and class and its ability to reach a large audience has been part of its appeal. The Handbook provides clear and informative essays by experts from a variety of disciplines, addressing the diverse and broad-based impact of race, gender, and class studies. The Handbookis aimed at undergraduate and graduate students who are looking for a basic history, overview of key themes, and future directions for the study of the intersection of race, class, and gender. Scholars new to the area will also find the Handbook’s approach useful. The areas covered and the accompanying references will provide readers with extensive opportunities to engage in future research in the area. © 2015 Shirley A. Jackson.
Keywords: dept.soc